(untitled) (Research, Society and Development, 2022)
Objective: To analyze the scientific production about the assessment of functional systems in the elderly Primary Health Care Method: Integrative literature review conducted in the databases of the Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO). Based on the guiding question and the PICO strategy, the descriptors, "Global Functionality" OR "Functional Systems" AND "Elderly" AND "Primary Health Care" OR "Home Care", and, "Functional Capacity" AND "Elderly" AND "Primary Health Care" OR "Home Care", with the Boolean operators AND and OR were used. Results: A total of four articles were analyzed after systematic selection, considering the inclusion and exclusion criteria and the proposed theme. Synthesized in a synoptic table with its main results and a flowchart and divided into three categories: Recognition of functional systems in the elderly; Primary Health Care/Home Care as actors in the aging process; Main alternatives and needs of functionality care. Conclusion: It is evident the precariousness of studies about the evaluation of the functional systems of cognition, mood, behavior and mobility of the elderly in Primary Health Care. It reaffirms the importance of using instruments in Primary Health Care that assess the functional systems of the elderly, for the planning and implementation of interventions, respecting the uniqueness and the life context of each elderly person.